Investigating Cultural and Social Factors in the Development of New Services in Children's Sports - Jalal Abdi; Zahra Hossein Pour; Mostafa Pasha Mokhtarian; Mohammadreza Amani; Mohammad Taghipour (International Journal of Children, 2025)
Cultural development is the foundation of true and sustainable development in all fields, including the sports system. The purpose of this research is to examine cultural and social factors in the development of new services in children's sports. We know that cultural and social factors are the most important dimension in the development of new services in children's sports. Therefore, by emphasizing and implementing activities to promote cultural and social factors, we can succeed in promoting other factors. The method of the present research is applied and information collection was carried out in two ways: library and field. In this research, two statistical communities were considered. The first statistical community is experts in related fields such as management, sports, entrepreneurship and children, of which the first sample includes twenty-five experts in management, sports, entrepreneurship and children. The sampling of the first community was accessible and purposeful sampling. The second statistical community includes sports coaches who work with children. The second statistical sample includes 212 sports coaches who work with children. The findings of the study support the idea that social and cultural elements positively impact the creation of new services in children's sports. These results demonstrate that in order to improve children's sports services, cultural understanding, social participation, and policy support must all be strengthened. The study also highlights how cooperation between athletic associations, legislators, and teachers can promote sustainability and creativity in children’s sports development.
Keywords: Children’s Sports; Cultural Development; Social Factors; Sports Services; Sustainability in Sports